Genetic diversity of 10 indigenous chicken ecotypes from Southern Highlands of Tanzania based on Major Histocompatibility Complex-linked microsatellite LEI0258 marker typing - Mwambene, Pius L.; Kyallo, Martina M.; Machuka, Eunice M.; Githae, Dedan; Pelle, Roger (Elsevier, 2019)
Unraveling the genetic diversity of livestock species is central to understanding their value and importance for conservation and improvement in diverse production environments. In developing countries, information on genetic attributes of many livestock species is unfortunately scanty to support well-informed decision-making upon relevant management strategies. This study aimed at investigating allelic variability, genetic diversity, and genetic relationships of 10 indigenous chicken ecotypes from Southern Highlands of Tanzania using the Major Histocompatibility Complex-linked LEI0258 marker. A total of 400 DNA samples, 40 per ecotype, were genotyped by capillary electrophoresis. Thirty different alleles with sizes ranging from 197 to 569 bp were determined. The number of alleles ranged from 17 (Itunduma) to 21 (Mbeya), with an average of 19.20 alleles per ecotype. Allelic polymorphism was further evaluated through genotyping by Sanger sequencing. Thirty-three DNA samples with different fragment sizes were re-amplified and their alleles sequenced to depict polymorphism based on a combination of two repeat regions at 12 and 13 bp, respectively, and flanking regions with SNP and indels. The repeat region at 13 bp appeared 1 to 28 times, whereas the region at 12 bp appeared 3 to 19 times in all sequenced fragments. The numbers of indels and SNP determined were 7 and 9, respectively. From capillary electrophoresis, the Chunya and Msimbazi ecotypes exhibited the highest genetic diversity (0.937), whereas the lowest value (0.910) was observed from the Mbarali ecotype, with an average of 0.925. The Namtumbo and Wanging'ombe ecotypes showed high inbreeding coefficients (FIS > 0.05), whereas a high excess heterozygote value (FIS = -0.098) was observed from the Njombe ecotype. Two percent of the genetic diversity was due to differences among ecotypes, and the rest was due to differences among individuals within the ecotypes. Despite the overall low genetic differentiation, both fragment and sequencing analyses depicted a high allelic and genetic variability across 10 chicken ecotypes. These results therefore, underscore the importance of establishing appropriate conservation and management strategies to capitalize on observed variability and maintain genetic flexibility across diverse production environments.